Effects of a cocoa diet on an intestinal inflammation model in rats (2012)
Cocoa is a rich source of fiber and flavonoids with recognized antioxidant and anti-inflammatory potential. The aim of this study was to evaluate the effects of a cocoa-enriched diet on rats with dextran sulfate sodium (DSS)-induced colitis. Wistar rats were fed with either a 5% cocoa diet or standard diet. Colon inflammation was induced by DSS in the drinking water: 5% for six days and 2% over the following nine days. Colitis was assessed by body weight loss, stool consistency and blood presence in stools. A group of animals fed standard diet was treated with quercitrin (1 mg/kg) after colitis establishment. After two weeks of DSS treatment, the colon oxidative and inflammatory status and lymphocyte composition from blood and mesenteric lymph nodes (MLNs) were assessed. The cocoa-fed group did not exhibit amelioration of clinical colitis but displayed higher antioxidant activity than the colitic reference group by the restoration of colon glutathione content and prevention of lipid peroxidation. The cocoa diet showed anti-inflammatory potential because it down-regulated serum tumor necrosis factor-?, colon inducible nitric oxide synthase activity and decreased colon cell infiltration. The lymphocyte composition in MLNs was not modified by drinking DSS, but there was an increase in the proportion of natural killer and regulatory T-cells in the blood. These changes were not modified by cocoa. In conclusion, cocoa intake may help to inhibit the negative oxidative effects consequent to colitis, although this action is not enough to abrogate the intestinal inflammation significantly.